Media Aura: An Analysis of the Mediatization of Contemporary Images - Monroy Galindo, Adriana; Soriano Clemente, Jaume (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Digital platforms and new information and communication technologies have changed how citizens interact with art. Prosumers, emerging as key players, have (re)appropriated images, including traditional works. A qualitative model is presented to understand prosumers' media engagement, revealing the meaning of their new role as producers. Grounded theory and sociosemiotic analysis are combined from a phenomenological perspective. This approach uncovers the complexities of art engagement on social media. Its adaptability suggests practicality in researching contemporary images, providing a framework to explore changing meanings in the digital age.